Adult education : DPH educaton series - Singh,U. K.; Sudarshan,K. N. (New Delhi : Ansari Road : Discovery publishing house, 1996)
Current Crisis in Adult Education, Adult Learners: Motives for Learning and Practice, Adult Development, Programme Development for Adults, The Process of Experimental Learning, Understanding How Adults Learn, The Role of the Adult Educator, Adult Life-world Concerns and Protection of the Commons, The Interpersonal Relationship in the Facilitation of Learning, Toward Guidelines for Good Practice.
Includes index.
Keywords: Current crisis in adult education -- Adult development -- Programme development for adults